The Relationship Of Job Insecurity, Affective Commitment, And Job Performance Post Covid-19 - Tari JN Syafitri; Laura Syahrul; Rahmi Fahmy (Institute of Computer Science (IOCS), 2022)
This study aims to examine the effect of Job Insecurity on Job Performance with Affective Commitment as a Mediating Variable Post Covid-19 Pandemic (Case Study: Four Star Hotel employees in Padang City). The data processing was carried out through Smart-PLS. There was a total of 155 samples collected using purposive sampling method. The results showed that a) job insecurity has a negative but not significant effect on employee performance, b) job insecurity has a negative and significant effect on affective commitment, c) affective commitment has a positive and significant effect on employee performance, d) affective commitment mediates the relationship between job insecurity on employee performance.